Brand Management Strategies for Sustainability: Insights from a Systematic Review - Wijaya, Fanji; Rahayu, Agus; Hendrayati, Heny (Business Education Program of Universitas Pendidikan Indonesia, 2024)
The literature review highlights the importance of sustainability in modern brand management strategies, highlighting green marketing, brand trust, brand equity, digital marketing, and Corporate Social Responsibility (CSR) as key pillars. Sustainability is now a core component of brand differentiation and reputation building, appealing to environmentally conscious consumers, and fostering long-term loyalty through transparent practices. Digital marketing is an effective channel for disseminating sustainability initiatives, aligning with shifting consumer behaviors towards sustainable consumption. CSR and sustainable development practices are increasingly incorporated into brand strategies, even in luxury markets. However, the review acknowledges limitations such as reliance on a single database, limited publication time frame, and a predominance of general findings over context-specific insights. Future research should incorporate multi-database sources, broaden the time range, and include qualitative and context-specific analyses. Triangulation techniques, such as practitioner interviews, are recommended to mitigate selection bias and strengthen the validity of findings. The review emphasizes the strategic importance of sustainability in brand management, urging companies to adopt sustainable practices to remain competitive and socially responsible, ultimately fostering long-term business resilience.